Application of machine learning in hepatocellular carcinoma - NIU Riyu; WANG Xin; LIU Dingjing; LI Chengzhong (Zhongguo linchuang yanjiu)
Hepatocellular carcinoma (HCC) is a common solid tumor. In recent years, although significant researches have been focused on diagnostic and therapeutic strategies for HCC, the overall prognosis for patients remains challenging. Machine learning (ML) , as a core technology of artificial intelligence, has been increasingly applied in the field of tumor research. Compared to traditional regression models, ML models excel at handling high dimensional data and complex nonlinear relationships, making it an ideal tool for HCC research. This review summarizes the application of ML in the risk prediction, diagnosis, treatment selection, and prognosis evaluation of HCC, aiming to provide references and insights for clinical practice and future research.